Pre-season football preparation in the era of COVID-19: Croatian Football Association model - Primorac, D.; Matišic, V.; Molnar, V.; Bahtijarevic, Z.; Polašek, O. (Journal of Global Health, 2020)
Although professional football players are generally a healthy population without chronic respiratory, cardiac, renal diseases, as well as other chronic conditions, we must take COVID-19 seriously and act accordingly before returning to football pitches. Underlying genetic factors must also be taken into ac-count as they might be aggravated by COVID-19 causing their clinical manifestation. Together with the list of medical examinations that players must undergo in order to be eligible to participate in UEFA competitions, we hereby propose a model for screening professional football players returning to the field after the lift of the ban on all sport activities because of the COVID-19 pandemic. Besides pre-sea-son physical examination (primarily 12-lead ECG, spirometry with bronchodilatation test, diffusing capacity of the lung for carbon monoxide (DLCO) test and fractional exhaled nitric oxide (FeNO) test) and medical examination defined by the UEFA Medical Regulations (for the next season), we are pro-posing that every football player from the Croatian first National League must have negative consecu-tive two RT-qPCR COVID-19 pharyngeal swabs over a 5-day interval. We propose that football players need a gradual return to physical activities during four separate phases. We believe that adherence to the recommendations and testing of players will drastically reduce the risk of them being exposed to SARS-CoV-2 and other pathogens. In turn, it should allow a steady return to football we all know and love